Audit Sistem Pembayaran Pada Sista Menggunakan Cobit 4.1 Di Universitas AKI Semarang - K, Marchel Haddyanto; Dharmawan, Alexander; Bakti, Cristeddy Asa (STIKOM Tunas Bangsa Pematangsiantar, 2026)
The payment system is a crucial component in the academic operations of higher education institutions. Universitas AKI Semarang has implemented the Integrated Information System (SISTA) to manage these financial transactions. This study aims to evaluate the IT governance of the SISTA payment system by measuring its maturity level using the COBIT 4.1 framework. The evaluation focuses on four key processes: DS2 (Manage Third-Party Services), DS11 (Manage Data), ME1 (Monitor and Evaluate IT Performance), and ME2 (Monitor and Evaluate Internal Control). A quantitative research method was employed, utilizing questionnaires distributed to relevant respondents. The results indicate that all assessed domains are at Level 3 (Defined Process), with specific maturity indices of 3.00 for DS2, 3.48 for DS11, 3.71 for ME1, and 3.80 for ME2. A gap analysis conducted against a target of Level 4 (Managed and Measurable) reveals a performance gap in every domain, with the largest discrepancy found in third-party service management (DS2). Based on these findings, a set of improvement recommendations has been formulated to enhance system management, ensuring it becomes more measurable, controlled, and sustainable